DIRECT DIGITAL TECHNOLOGY FOR CERAMIC DENTAL BRIDGE REALIZATION - Diana Diaconu-Popa (Romanian Journal of Oral Rehabilitation, 2021)
Digital technologies-Computer Aided Design-Computer Aided Manufacruring (CAD-CAM) are constantly improving, equipment and materials becoming more and more efficient; the main goal is to perform as many of the prosthetic restorations directly in the dental office, eliminating the intervention of the dental laboratory. This article aims to present the steps of a dental ceramic bridge realization, using direct CAD-CAM technology, the subtractive method. Minimizing the treatment time and number of appointments is not only favorable for the patient but also excludes possible complications during the treatment, allowing to obtain optimal prosthetic appliances, with a simplified workflow. Patients want to benefit from a quick treatment, which does not cause discomfort, and which ensures a complete restoration of all the functions of the dento-maxilar system.